Cancer stem cell markers in triple-negative breast cancer : a comparison between patient biopsies and cancer cell models - Vieira, Ana Margarida Novais da Costa (2024)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2024